„Wezwanie” – pismo literackie drugiego obiegu wydawniczego (1982–1989) - Nolbrzak, Renata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
“Wezwanie” was the first underground socio-cultural magazine published during martial law. The individual who had the greatest influence on “Wezwanie” was Tomasz Jastrun – the magazine’s founder, and an editor and author. Thanks to his determination, the publication appeared continuously for nearly eight years. It was published until June 1989, and was printed, in turn, by the following publishing houses: Copyright, Przedświt and Oficyna Wydawnicza Pokolenie. There were 15 issues of the magazine printed, each having 100–200 pages, with circulations of 1000–2000 copies. “Wezwanie” mainly published literary works, including all types of testimonies: diaries, descriptions of police suppression, relations of persecution. An important place in the magazine was occupied by poetry. This included poems written by many well-known poets, such as Herbert, Krynicki, Zagajewski, Szaruga, and Jastrun. Furthermore, the magazine featured stories (e.g. Marek Nowakowski and Kazimierz Orłoś), interviews (e.g. with Kazimierz Brandys, Vladimir Bukowski and Janusz Głowacki), editorial discussions, reviews of events, reviews of press, lists of new books, and reviews.